Anemia Profile in Pediatric Patients at Pediatric Intensive Care Unit (PICU) of Dr. Soetomo General Academic Hospital - Larasati, Sarah Ayu; Setyaningtyas, Arina; Hanindito, Elizeus; Andarsini, Mia Ratwita (Indonesian Journal of Anesthesiology and Reanimation, 2022)
Introduction: Anemia often occurs in critically ill children and is associated with increased morbidity and mortality in women and children and impaired cognitive and behavioral development in children. Objective: This study aims to understand the profile and characteristics of anemia patients in the critical care population. Methods: This is a retrospective, descriptive study of the patient's medical records. Data were collected by the total sampling technique. Results: Among 203 patients, 52% were anemic at admission to the Pediatric Intensive Care Unit (PICU), while 45% were anemic at discharge. Anemia tends to be more common in older age and male individuals with their chief complaints being respiratory symptoms, higher mean Red Cell Distribution Width (RDW) levels, and poorer nutritional status. There were 84 patients (41%) who received Packed Red-Cells (PRC) transfusions, among them there were 54 patients (51%) who were anemic at PICU admission. Of the 84 patients who received PRC transfusions during their PICU stay and 43 patients (47%) were anemic on PICU discharge. Conclusion: Anemia is quite common in critically ill children and is dominated by male patients aged under 5 years. Anemia also mostly happens in patients with higher organ dysfunction scores and poorer nutritional status than nonanemic patients. Half of the patients with anemia at the PICU also received PRC blood transfusion.